The structure of a “strange language” in the text of an Ukrainian folk charm (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
In the article the author analyses the structure of a “strange language” in the text of an ukrainian folk charm which reflects the usage of Ukrainian wordforming morphemes, grammar forms and meanings, rhythmic composition.
Keywords: folk charm; a “strange language”; structure